Relational and sexual satisfaction during military deployment: a comparative study - Esteves, Higino (2022)
Military deployments in International Military Missions are a frequent reality for the Portuguese (PRT) military members. Despite the increasing number of researches on post deployment adjustment of military couples, gaps remain on studies focused on the periods of the deployment, namely during the period of physical/geographical separation. In particular, the impact of these missions in couple's adjustment on communication and on both romantic and sexual satisfaction have been poorly studied with this population (Barbudo, Francisco & Santos, 2014). The purpose of this cross-sectional study was to compare the investment on relationship and the satisfaction with communication, with sexuality and with relationship between a group of Portuguese Military service members during their long-term deployment in International Military Missions and a group of similar soldiers that work in their hometowns.